Immunisation status of children presenting to the emergency department: Linkage of a longitudinal birth cohort with national immunisation data. (31st October 2018) - Keijzers, Gerben; Sweeny, Amy; Crilly, Julia; Good, Norm; Cameron, Cate M; Mihala, Gabor; Thone, Jae; Scuffham, Paul A
Abstract : Aim: To describe the relationship between emergency department (ED) diagnosis of infectious disease and immunisation status in children ≤5 years. We also aimed to demonstrate feasibility of proof‐of‐concept linkage between disparate databases. Methods: Data from a cohort of 3404 children born in Southeast Queensland/Far North New South Wales between 2006 and 2011 were linked to Australian Childhood Immunisation Registry data and Emergency Department Information System data for presentations between 2006 and 2014. Immunisation status was assigned using the 2009 National Immunisation Program schedule. Results: Of 1490 children (79% of those consented) with data on immunisation status, 87.2 and 84.6% were fully immunised by 12 and 24 months, respectively. Adding partially immunised children increased this to 93.2 and 91.4% at 12 and 24 months, respectively. Nearly two‐thirds of all children made at least one ED presentation. Children presenting to ED with an infectious disease did not differ in immunisation status compared to children with other (non‐infectious disease type) presentations but were younger, more likely to live with other children and had a longer ED stay and higher admission rate. Respiratory syncytial virus (RSV) was more frequently diagnosed in unimmunised children. Conclusions: In an existing birth cohort, immunisation rates were lower than the national average. RSV was more prevalent in unimmunised children presenting to ED, but immunisation status was not significantly associated with other infectious disease presentations. Linkage between national immunisation data and Australian ED data is feasible and has the potential to identify previously unrecognised factors related to child immunisation status and health‐care utilisation.